The legal system of the investment environment in the public sector - Abd Hussein, Shafaa (Opción, 2019)
The investment is intended to invest money in any economic activity or project that benefits the country. The proper employment of oil resources is contributed by the sound environment to invest in achieving sustainable development in general and the economy of the country in particular. It is divided into public and private investments. Governmental organization to satisfy public needs and usually through the national institutions or compa- nies competent as the national oil company established by the law of the establishment of the Iraqi National Oil Company No. 11 of 1964 and amen- ded by Law No. 123 of 1967, which resorted to Iraq in the development of industry The private investment refers to that investment which comes as a result of the initiative of a natural or legal person alone to invest in a particu- lar project to obtain profit and interest. The private companies owned by one of the people of the private law that invest their money for the purpose of making profit, and the investment is achieved under certain conditions related to the nature of money Investor and the nature of the investor and is under the legislative guarantees of the objective and formality (procedural) requires the text to achieve the best investment.